2009
DOI: 10.1097/mco.0b013e3283186f59
|View full text |Cite
|
Sign up to set email alerts
|

The geriatric nutritional risk index

Abstract: In maths of nutrition 'recognize and treat' has become a clinical imperative. Actually, clinical judgement by an expert is still considered the reference standard to diagnose malnutrition but the use of simplified tools profitably assists in nutritional risk screening process. The GNRI is easy to use and preliminary results show that it is promising. Its routine application, next to the other validated tools already available, might be enforced in the assessment of the old patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
113
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 43 publications
4
113
0
2
Order By: Relevance
“…Third, our study demonstrated that malnourishment was a critical determinant in modifying the low SUA‐associated mortality. Moreover, GNRI, the nutritional screening tool in our study, was clinically more useful because it is well‐validated, less time‐consuming, and did not require skilled personnel 42. Furthermore, GNRI has a higher prognostic value for classification of nutrition‐related complication in elderly patients than the Mini‐Nutritional Assessment test 27.…”
Section: Discussionmentioning
confidence: 80%
“…Third, our study demonstrated that malnourishment was a critical determinant in modifying the low SUA‐associated mortality. Moreover, GNRI, the nutritional screening tool in our study, was clinically more useful because it is well‐validated, less time‐consuming, and did not require skilled personnel 42. Furthermore, GNRI has a higher prognostic value for classification of nutrition‐related complication in elderly patients than the Mini‐Nutritional Assessment test 27.…”
Section: Discussionmentioning
confidence: 80%
“…Ideal body weight was calculated using the formula: 22xsquare of height in metres 20. Patients with GNRI >98 have normal nutritional status, those with GNRI 92–98, 82–91, <82 have mild, moderate and severe malnutrition, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The ideal body weight was calculated using height and an idealized BMI of 22 kg/m 2 [15,17]. Clinical characteristics and adverse clinical outcomes were compared in groups with GNRI < 92 (defined as moderate or severe nutrition-related risk) and ≥92 (defined as low or no nutrition-related risk) [23,24,25]. …”
Section: Methodsmentioning
confidence: 99%